Effects of Social Media Usage & Their Attitudes of Management Students - Rashi P. Thakkar (International Journal of Advanced Science and Technology, 2020)
Social media has become necessity for daily survival and the humans getting affected by it the most are the youngsters of age 18-30 years especially college going students. This paper shows the relationship that how usage of social media is impacting the routine of management students. This study examined in what areas is the social media affecting them specifically and how do they react to it which also helps us judge their attitude towards social media. A survey was conducted with post-graduate students pursuing/ passed out management students that how is their life, studies getting affected by social media and it what level it influences you to stick to it. From the survey results we can see that management students have reported a positive side that there is high usage of social media not only on daily basis but most of the time its every hour. If surfing on social media site is off another site gets it attention. This interference is also seen during their work hours which in between triggers themselves to go with the flow of social media content, that helps them distract completely from what they are supposed to do at the present moment.